PEMBUATAN NANOPARTIKEL PERAK (NPP) DENGAN BIOREDUKTOR EKSTRAK BUAH Muntingia calabura L UNTUK ANALISIS LOGAM MERKURI - Purwo Ismaya Sari; M. Lutfi Firdaus; Rina Elvia (University of Bengkulu, 2017)
The goal of this research was to make silver nanoparticles (NPP) with a cherry fruit extract bioreductor which was used for mercury metal analysis by using a digital image method. The process of making silver nanoparticles had done by a bottom up method involving a reduction reaction. The precursors used were 1 mM AgNO3 solution and as a bioreductor was an antioxidant compound which were in cherry fruit extract. Variation of the volume ratio between cherry fruit extract and 1 mM AgNO3 solution was 1: 3, 1: 4, 1: 5, 1: 6, and 1: 7 and the variation of contact time were 5, 15, 30, 45, 1, 2, 3 hours, and 1, 2, 7 days. The most optimum results of silver nanoparticles were synthesized with 1 : 4 volume ratio and 1 hour contact time. From the results of selectivity test, it was known that silver nanoparticles were made selective toward Hg and Fe metal. The sensitivity test toward Hg metal, it was known that NPP can detect mercury metal with the smallest concentration of 16,7 ppb.